KESELAMATAN KERJA DALAM PERSPEKTIF MAQASHID AL SYARIAH - Maryam, Bismi Nursyamsia; Maloko, M. Thahir (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
This study aims to find out how the application of occupational safety in Parepare City, using field research (qualitative). Although in 2019 and 2020 Parepare City is not a city with zero accidents, but in general, the implementation of occupational safety has gone well and in accordance with the provisions of laws and regulations, especially for UP3 PLN Parepare City and Pertamina Fuel Terminal Parepare City which have consistently implemented a system of supervision, control and evaluation as part of the Occupational Safety and Health Management System (SMK3). In the concept of Maqashid al Syariah, life safety ranks second only to the obligation to maintain religion, if the concept is used to examine aspects of safety in labor, then maintaining the soul of each worker is not only an obligation of each worker, but also by the employer (company) and the government as a regulator.